Kearns–Sayre syndrome caused by defective R1/p53R2 assembly. Issue 9 (4th March 2011) - Pitceathly, Robert D S; Fassone, Elisa; Taanman, Jan-Willem; Sadowski, Michael; Fratter, Carl; Mudanohwo, Ese E; Woodward, Cathy E; Sweeney, Mary G; Holton, Janice L; Hanna, Michael G; Rahman, Shamima
Abstract : Background: Mutations in RRM2B encoding ribonucleotide reductase (RNR) p53R2 subunit usually cause paediatric-onset mitochondrial disease associated with mitochondrial DNA (mtDNA) depletion. The importance of RNR dysfunction in adult mitochondrial disease is unclear. Objective: To report the RRM2B mutation frequency in adults with multiple mtDNA deletions and examine RNR assembly in a patient with Kearns–Sayre syndrome (KSS) caused by two novel RRM2B mutations. Methods: 50 adult patients with multiple mtDNA deletions in skeletal muscle were studied. DNA sequencing of RRM2B was performed in patients without mutations in mtDNA maintenance genes POLG and C10orf2 . RNR protein was studied using western blot and Blue-native polyacrylamide gel electrophoresis (BN-PAGE). Results: Four per cent (two unrelated cases) of this adult cohort harboured RRM2B mutations. Patient 1 had KSS and two novel missense mutations: c.122G→A; p.Arg41Gln and c.391G→A; p.Glu131Lys. BN-PAGE demonstrated reduced heterotetrameric R1/p53R2 RNR levels compared with controls, despite normal steady-state p53R2 levels on western blot, suggesting failed assembly of functional RNR as a potential disease mechanism. Patient 2 had late-onset progressive external ophthalmoplegia and fatigue. A heterozygous deletion c.253_255delGAG; p.Glu85del was identified. Muscle histology in both cases showed significant numbers of necrotic muscle fibres, possibly indicating enhanced apoptotic cell death. Conclusion: These data indicate that 4% of adult mitochondrial disease with multiple deletions is caused by RNR dysfunction. KSS has not previously been linked to a nuclear gene defect. Evidence that disease pathogenesis may be caused by defective RNR assembly is given. RRM2B screening should be considered early in the differential diagnosis of adults with multiple mtDNA deletions.